Knowledge sharing behavior and traits emotional intelligence in police forces - Ruslan, Shazrin Azlin; Jantan, Amer Hamzah; Zawawi, Dahlia; Zainudin, Zanurul Huzaima (Human Resource Management Academic Research Society, 2016)
Knowledge sharing is exclaimed able enhance the quality of the public sector system and increase the productivity of personnel in the public sector. Police forces are a significant and essential part of the public sector. Research suggested that in order to foster knowledge sharing among public sector personnel, it is important to understand the factors affecting the employees’ interest to share knowledge. It is also believed that individual characteristics play a major role in knowledge sharing behaviour. This study aims to examine the Knowledge Sharing Behaviour from personality differences and relationship of variances of personality with decision-emotions among police officers as explained by the Trait Emotional Intelligence.